MAIN TYPES OF CONTRACTS IN ISLAMIC FINANCE AND THEIR SHARE IN THE FINANCIAL MARKETS (World Economics and Finance Bulletin, 2022)
In this paper, I will try to put a light on the main types of contracts in Islamic Finance. The main differences of these Islamic Financial equities have been explained. Moreover, there has been provided a comparison analysis of conventional financial instruments and Islamic Financial instruments.
Keywords: Islamic Finance; Musharakah; Mudarabah; Murabahah